Dekonsentrasi Aset Muhammadiyah: Model Tata Kelola Organisasi Keagamaan dalam Perspektif Keadilan Distributif - M Shoim; Abdul Halik; Siti Mujanah (Universitas Pendidikan Ganesha, 2026)
The phenomenon of uneven national asset concentration in Indonesia serves as the backdrop for this study. Amidst this condition, Muhammadiyah emerges as an institutional outlier with an asset deconcentration model that distributes wealth through a widespread network of charitable enterprises. This article aims to construct a conceptual model of Muhammadiyah's asset deconcentration within a distributive justice framework and to formulate theoretical propositions derived from this practice. Employing a qualitative approach through content and document analysis of primary and secondary sources from the 2010–2025 period, this study finds that Muhammadiyah's asset deconcentration operates through three integrated mechanisms: structural decentralization, sectoral diversification, and cadre regeneration, with productive waqf as a key instrument. The study also identifies a dialectical tension between legal-formal centralization and operational decentralization, which paradoxically serves as a long-term asset protection mechanism. As a theoretical contribution, this article proposes that the combination of centralized ownership and decentralized management in faith-based organizations is a significant determinant of the sustainability of economic benefit distribution. This model offers a wealth redistribution pathway that does not rely entirely on state or market mechanisms and holds cross-contextual relevance for asset management in faith-based organizations in developing countries.